Integrating Marine Problems as Suplementary for Trigonometry Topic in Nautical Fishing Vessel Program - Tambunan, Muhammad Al Azhari; Jamiah, Yulis; Siregar, Nurfadilah; Rif'at, Mohamad; Hartoyo, Agung (Edumatika, 2023)
The students of the Nautical Fishing Vessel (Nautika Kapal Penangkap Ikan or NKPI) program at the State Secondary Fisheries Business School (Sekolah Usaha Perikanan Menengah Negeri or SUPMN) Pontianak cannot solve maritime problems properly, for example, shipping problems. One of the reasons is that maritime problems have not been integrated into the competency achievement indicators of Trigonometry topic. The aims of this research are to produce supplement of Trigonometry textbook that incuded marine problems. This research is a research and development (R&D) with 4D (define, design, develop, and disseminate) model. Data collection uses questionnaires, interviews, validation sheets, and maritime problem-solving test. The analytical techniques used include descriptive analysis and calculating the sign-test. The research results show that the supplement of Trigonometry textbook had a good impact on students’ skill in solving marine problems.